Metals, oxidative stress and neurodegeneration - Bush, Ashley (Henry Stewart Talks, 2007)
Production of reactive oxygen species (ROS), Chemical origin, Generic mechanism of protein and transition metal combination, Pathological protein aggregates, Toxic ROS generation, Role in etiology and tissue specificity of agedependent neurodegenerative diseases
Reviewed at 2020/08/13